1995
DOI: 10.1016/0092-8674(95)90335-6
|View full text |Cite
|
Sign up to set email alerts
|

Sgs1: A eukaryotic homolog of E. coil RecQ that interacts with topoisomerase II in vivo and is required for faithful chromosome segregation

Abstract: Topoisomerase II (topo II) catalyzes the decatenation of interlinked DNA molecules and is essential for chromosome segregation. To test the hypothesis that the noncatalytic C-terminal domain of topo II is necessary for mediating interactions with other proteins required for chromosome segregation, we used a two-hybrid cloning strategy to identify proteins that interact with S. cerevisiae topo II in vivo. One protein identified (Sgs1p) is structurally related to E. coli RecQ protein and contains helicase signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
330
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(340 citation statements)
references
References 31 publications
10
330
0
Order By: Relevance
“…Functional interaction between proteins involved in DNA replication, such as replication protein A (RPA) and DNA polymerase ␦, and WRN also have been reported (Shen et al, 1998;Brosh et al, 1999;Kamath-Loeb et al, 2000). Furthermore, in yeast, the RecQlike proteins seem involved in suppression of hyperrecombination, S-phase checkpoint control, and correct DNA segregation (Gangloff et al, 1994, Watt et al, 1995Stewart et al, 1997;Davey et al, 1998;Yamagata et al, 1998;Frei and Gasser, 2000). Noteworthy, yeast mutants in such RecQ-like helicases are extremely sensitive to agents that cause replication arrest, such as hydroxyurea because of uncontrolled illegitimate recombinational events (Stewart et al, 1997;Yamagata et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Functional interaction between proteins involved in DNA replication, such as replication protein A (RPA) and DNA polymerase ␦, and WRN also have been reported (Shen et al, 1998;Brosh et al, 1999;Kamath-Loeb et al, 2000). Furthermore, in yeast, the RecQlike proteins seem involved in suppression of hyperrecombination, S-phase checkpoint control, and correct DNA segregation (Gangloff et al, 1994, Watt et al, 1995Stewart et al, 1997;Davey et al, 1998;Yamagata et al, 1998;Frei and Gasser, 2000). Noteworthy, yeast mutants in such RecQ-like helicases are extremely sensitive to agents that cause replication arrest, such as hydroxyurea because of uncontrolled illegitimate recombinational events (Stewart et al, 1997;Yamagata et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…In budding yeast, a single RecQ member is encoded by the SGS1 gene. It is a 3 -5 DNA helicase (Bennett et al, 1998) interacting with topoisomerases Top3 and Top2 (Gangloff et al, 1994;Watt et al, 1995). Another ATP-dependent DNA helicase with 3 -5 polarity, playing a role in genome stability, is encoded by the MPH1 gene from Saccharomyces cerevisiae (Scheller et al, 2000;Prakash et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The BLM protein has been identi®ed as a member in the DExH boxcontaining RecQ helicase subfamily (Ellis et al, 1995). Its primary sequence presents similarities with all known members in the RecQ subfamily, including Escherichia coli RecQ (Umezu et al, 1990), Saccharomyces cerevisiae Sgs1p (Ganglo et al, 1994;Watt et al, 1995), Schizosaccharomyces pombe Rqh1 (Stewart et al, 1997), Drosophila melanogaster DmBLM (Kusano et al, 1999), human RecQL (Puranam and Blackshear, 1994;Seki et al, 1994), human Wrn, the product of the Werner's syndrome gene (Yu et al, 1996) and the recently identi®ed human RecQ4 and RecQ5 proteins (Kitao et al, 1998). Chester et al (1998) developed a mouse model for the human Bloom's syndrome, and showed that mouse embryos homozygous for a targeted mutation in the murine Bloom's syndrome gene die by embryonic day 13.5, but little is known about function(s) of BLM.…”
Section: Introductionmentioning
confidence: 99%